Pelatihan Peningkatan Kewirausahaan dengan Strategi Komunikasi Persuasif Bagi Kader Gerbangmas: Desa Selok Awar-Awar Kabupaten Lumajang - Fauziah, Anisatul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
Entrepreneurship improvement training aims to develop communication skills. Selok Awar-Awar Awar-Awar village, Pasirian Lumajang sub-district is a very potential tourist spot for people to entrepreneurship. By exploiting the potential of natural resources (SDA) and human resources (HR), it can be assured regional income will increase. In addition, by exploiting the natural potential, the field of work will increase and the unemployment rate will decrease. However, in reality people have not taken advantage of entrepreneurship opportunities as well as possible. This is due to their lack of knowledge about entrepreneurship. Most people tend to think only about how to create and process products, they are less concerned about how to promote their products to sell and excel in the market with a high price. For that, the need for training marketing the product with a persuasive language or with a language that can mensugesti consumers.